PELATIHAN PENINGKATAN PENGUASAAN KOSA KATA BAHASA INGGRIS DENGAN TEKNIK MENYANYI DAN MENGGUNAKAN FLASH CARDS BAGI SISWA-SISWI SDN 1 KESIUT - Ni Made Ayu Widiastuti (Buletin Udayana Mengabdi, 2020)
The English trainings given to the students in the 4th and 5th grades in SDN 1 Kesiut aims at finding out the topics of the English lessons in their English books in order to know the vocabulary given in the training, and describing the results of the training by using flash cards and singing technique. The trainings were given four times during the program, with the duration of 1,5 hours on each meeting and each class. The topics in the 4th grade English book are “I buy hat’, “It’s raining today”, “Went to Borobudur”, and “Let’s have fun”, and in the 5th grade are “I am cooking”, “We are at school”, “I like pizza”, and “My red cap”. The results show that the students are able to enhance the mastery of the English vocabulary after the training. The use of flash cards improved the vocabulary mastery between 19% - 47% (class 4), and 1% - 20% (class 5). Moreover, by applying singing technique, the improvement shown by the 4th grade students is approximately 16% - 48 %, and it is around 9% - 38% shown by the 5th grade students. Key words : training, improvement, English vocabulary, flash cards, singing